Analysis of The Javan Green Peafowl (Pavo muticus muticus Linnaeus 1758) Habitat in Baluran and Alas Purwo National Park, East Java - Jarwadi Budi Hernowo; Cecep Kusmana; Hadi Sukadi Alikodra; Ani Mardiastuti (Bogor Agricultural University, Indonesia, 2018)
Information of javan green peafowl habitat is commontly informate as general and only discribing typical habitat used. Details information and data of the componen habitat, availability and function such as (food resources, shelter, cover, drinking site, nesting site, etc), and characteristic function of habitat componen at every habitat type are very important to be known how habitat component support to the javan green peafowl live Baluran and Alas Purwo national park is one of distribution javan green peafowl and it was choosen to study on the habitat analysis. The research was aimed to is to analysis and synthesis of availability, fucntion and characteristic habitat of javan green peafowl and to descripbe of ideal habitat for javan green peafowl. Vegetation analysis was used as method approach to obtain composition, structure of vegetation and potential food, shelter, cover and nesting site. Base on activities of the bird and combaining with use of habitat component, analysis of habitat used was done. The result showed that javan green peafowl get food at open area and feed much on grasses and shrubs.Drinking site is areal where water available contiously. The characteristic of feeding site is open area which is growth by grasses and shrubs. The shelter sites were used by the birds such as trees or ground bellow trees where are closed to feeding site. Characteristic roosting site is tall trees (emergent trees), the leaves are not dense, rather open, the branches of the trees form a relatively upright angle to the stem, and not far from the trees present the open area. The green peafowl select nest places at open area which is grow by shrubs and put the eggs at the ground. The ideally habitat of the javan green peafowl composed by open area which is growing by grasses and shrubs as feeding site, places where water resources available as drinking site, tree or shaded places as sheltering and resting site, tree, forest or dense shrubs for covering/refuge site, dust places for dusting activities, open area for dancing and open area which is growing by shrubs for nested places were compound closed each other.